Using Radiocarbon Measurements of Dissolved Inorganic Carbon to Determine a Revised Residence Time for Deep Baffin Bay - Zeidan, Sara; Walker, Jennifer; Else, Brent G. T.; Miller, Lisa A.; Azetsu-Scott, Kumiko; Walker, Brett D. (Frontiers in Marine Science, 2022)
The Arctic Ocean is warming at three times the rate of the rest of the planet and the effects of climate change on the Arctic marine carbon cycle processes remain unconstrained. Baffin Bay is a semi-enclosed, Arctic basin connecting to the Labrador Sea to the south. While the physical oceanography of surface Baffin Bay is well characterized, less is known about deep water formation mechanisms within the Basin. Only a few residence-time estimates for Baffin Bay Deep Water (BBDW) exist and range from 20 to 1450 years. Better residence time estimates are needed to understand how Baffin Bay will respond to climate change. Here we report stable carbon (δ13C) and radiocarbon (∆14C) values of DIC collected aboard the CCGS Amundsen in 2019. We observed DIC δ13C and ∆14C values between 0.7‰ to +1.9‰ and -90.0‰ to +29.8‰, respectively. Surface DIC δ13C values were between +0.7‰ to +1.9‰, while deep (>100m) values were 0.0 to -0.7‰. Surface DIC ∆14C values ranged between -5.4‰ to +22.9‰, while deep DIC (>1400m) DIC ∆14C averaged -82.2±8.5‰ (n = 9). To constrain natural DIC ∆14C values, we quantified the amount of atmospheric “bomb” 14C in DIC (∆14Cbomb; using the potential alkalinity method; Palk) and anthropogenic DIC (DICanth; using the ∆C* method). Both proxies indicated an absence of ∆14Cbomb and DICanth below 1000m. Using two previously proposed deep water formation mechanisms and our corrected DIC ∆14Cnatural values, we estimated a 14C-based residence time of 360-690 years for BBDW. Based on these residence times, we infer carbon is likely stored for centuries in deep Baffin Bay.